-2(6y+9)-3(4+5y)=0

Simple and best practice solution for -2(6y+9)-3(4+5y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6y+9)-3(4+5y)=0 equation:


Simplifying
-2(6y + 9) + -3(4 + 5y) = 0

Reorder the terms:
-2(9 + 6y) + -3(4 + 5y) = 0
(9 * -2 + 6y * -2) + -3(4 + 5y) = 0
(-18 + -12y) + -3(4 + 5y) = 0
-18 + -12y + (4 * -3 + 5y * -3) = 0
-18 + -12y + (-12 + -15y) = 0

Reorder the terms:
-18 + -12 + -12y + -15y = 0

Combine like terms: -18 + -12 = -30
-30 + -12y + -15y = 0

Combine like terms: -12y + -15y = -27y
-30 + -27y = 0

Solving
-30 + -27y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + -27y = 0 + 30

Combine like terms: -30 + 30 = 0
0 + -27y = 0 + 30
-27y = 0 + 30

Combine like terms: 0 + 30 = 30
-27y = 30

Divide each side by '-27'.
y = -1.111111111

Simplifying
y = -1.111111111

See similar equations:

| 130+35+X=180 | | 4m^2+17m-22=0 | | 9-3y=(-7)-4y | | 3n+5=40-4n | | 10(s-5)=-159 | | x-y+3z=10 | | -9(k-17)=-54 | | 19(k-17)=-54 | | 5120+50x+0.2x^2=0 | | n+1=99 | | 3/5x=7/2 | | X^2-3x-45=4x-1 | | M+2n=10 | | 1/8x=9/5 | | 5*3=39 | | 3z+4=4z-2 | | 3b-8=2-8b | | 3(3s+2)=69 | | 3x+30=x-14 | | x^2+bx+37=0 | | 8-m=log(3c+6) | | x+75=3x-5 | | 4a+5=3a+5 | | 4(x-10)=2x+20 | | 7x+2+-3x=-2 | | 35-2v=3v+5 | | 7z-14=34-z | | 1.3x-4/5=3.1 | | N+n+n=62 | | 3n=62 | | n+10=80 | | x=86+(-2y)+84+(-2y) |

Equations solver categories